2024
DOI: 10.21037/gs-23-433
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in the management of ductal carcinoma in situ in Republic of Korea: a comprehensive analysis using Health Insurance Review and Assessment data [2009–2020]

Ji Hyeon Joo,
Wontaek Kim,
Jiho Nam
et al.

Abstract: Background Increasing rates of diagnosis of ductal carcinoma in situ (DCIS), given the widespread use of mammography, is a global trend. Various attempts have been made in the selection of surgical methods and application of radiation therapy (RT), and the prevalence of infectious diseases has also affected these attempts. This study aimed to investigate evolving treatment patterns and trends in the management of DCIS in South Korea. Methods We conducted a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Multiple prospective randomized clinical trials have confirmed that whole-breast irradiation (WBI) effectively controls tumor growth at the primary site ( 29 , 30 ). Currently, in the United States and South Korea, the optimal treatment for DCIS is BCS, followed by WBI ( 31 ). In 2010, the Early Breast Cancer Trialists’ Collaborative Group (EBCTCG) conducted a representative meta-analysis that supported these treatment trends.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple prospective randomized clinical trials have confirmed that whole-breast irradiation (WBI) effectively controls tumor growth at the primary site ( 29 , 30 ). Currently, in the United States and South Korea, the optimal treatment for DCIS is BCS, followed by WBI ( 31 ). In 2010, the Early Breast Cancer Trialists’ Collaborative Group (EBCTCG) conducted a representative meta-analysis that supported these treatment trends.…”
Section: Discussionmentioning
confidence: 99%